Acquiring Clinical Knowledge from an Online Video Platform: A Randomized Controlled Experiment on the Relevance of Integrating Anatomical Information and Clinical Practice. Issue 5 (16th November 2018) - Grosser, Johannes; Bientzle, Martina; Shiozawa, Thomas; Hirt, Bernhard; Kimmerle, Joachim
Abstract : Basic subjects in medical education, such as anatomy, are often taught through teaching formats that do not always sufficiently demonstrate the relevance of this basic information for clinical practice. Accordingly, it is a recent trend in anatomy education to link anatomical information more explicitly to clinical practice. This article presents an online video platform (Tuebingen's Sectio Chirurgica [TSC]) as one means of explicitly integrating preclinical anatomical knowledge and clinical application. The purpose of the study presented here was to examine the effects of videos through which medical students were educated about Anterior Cruciate Ligament reconstruction. A TSC video about this surgical procedure was compared to a video with a traditional lecture providing the identical information. Participants ( n  = 114) perceived the TSC video to be superior in comprehensibility of the presentation ( P  = 0.003) and conceivability of the surgical procedure ( P  = 0.027), and to be more entertaining ( P  < 0.001). Moreover, participants in the TSC condition acquired more clinical knowledge than in the lecture condition ( P  = 0.043) but did not differ in their acquisition of anatomical knowledge. Mediation analyses indicated that the effect on the acquisition of clinical knowledge was mediated by comprehensibility, conceivability, and entertainment. These findings are discussed regarding their implications for medical education in terms of contributing to the general trend of linking preclinical anatomical knowledge to clinical application. A discussion about the limitations of the study and suggestions for future research are also provided.